Amniotic band associated with human tail-like cutaneous appendage and spinal dermoid tumor: An exceedingly rare triad - Leopoldo Mandic Ferreira Furtado; José Aloysio da Costa Val Filho; Bruno Lacerda Sandes; Gustavo Alberto Rodrigues da Costa; Fernando Levi Alencar Maciel; Eustaquio Claret dos Santos Júnior (Brazilian Society for Pediatric Neurosurgery, 2020)
Introduction: The association between amniotic band syndrome (ABS) and spinal dysraphism is an extremely rare entity that was paucity reported in the literature so far and similar conditions such multiple asymmetric encephaloceles and anencephaly were also previously described with ABS. Methods: In this case report, we described a male newborn in whom ABS was associated with human tail and lumbar dysraphism. A surgical approach was performed with intraoperative neurophysiological monitoring in which the tail and amniotic band were en bloc resected with favorable outcome. Dermoid tumor was identified by histopathological analysis Conclusion: The occurrence of spinal dysraphism combined with ABS should be managed carefully in order to avoid spinal cord damage. provides very good results for a number of indications in children. Every effort should be made to optimize the selection of surgical candidates on the basis of their clinical features.